Novel Mitochondria-targeted Drugs for Cancer Therapy - Fialova, Jindriska Leischner; Raudenska, Martina; Jakubek, Milan; Kejik, Zdenek; Martasek, Pavel; Babula, Petr; Matkowski, Adam; Filipensky, Petr; Masarik, Michal (Mini reviews in medicinal chemistry, 2021)
The search for mitochondria-targeted drugs has dramatically risen over the last decade. Mitochondria are essential organelles serving not only as a powerhouse of the cell but also as a key player in cell proliferation and cell death. Their central role in the energetic metabolism, calcium homeostasis and apoptosis makes them an intriguing field of interest for cancer pharmacology. In cancer cells, many mitochondrial signaling and metabolic pathways are altered. These changes contribute to cancer development and progression. Due to changes in mitochondrial metabolism and changes in membrane potential, cancer cells are more susceptible to mitochondria-targeted therapy. The loss of functional mitochondria leads to the arrest of cancer progression and/or a cancer cell death. Identification of mitochondrial changes specific for tumor growth and progression, rational development of new mitochondria-targeted drugs and research on delivery agents led to the advance of this promising area. This review will highlight the current findings in mitochondrial biology, which are important for cancer initiation, progression and resistance, and discuss approaches of cancer pharmacology with a special focus on the anti-cancer drugs referred to as 'mitocans'.
Keywords: Mitochondria; tricarboxylic acid cycle; hexokinase; targeting; Drug Screening Assays, Antitumor; Humans; electron transport chain; buněčná smrt; Antineoplastic Agents; cancer; lidé; mitochondrie; proliferace buněk; treatment; metabolism; Cell Proliferation; Neoplasms; screeningové testy protinádorových léčiv; inhibitors; protinádorové látky; nádory; respiratory chain; Cell Death